2009
DOI: 10.1016/j.yjmcc.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein impairs coronary arteriolar dilation to prostacyclin synthase activation: Role of peroxynitrite

Abstract: Endothelium-derived vasodilators, i.e., nitric oxide (NO), prostacyclin (PGI 2 ) and prostaglandin E 2 (PGE 2 ), play important roles in maintaining cardiovascular homeostasis. C-reactive protein (CRP), a biomarker of inflammation and cardiovascular disease, has been shown to inhibit NOmediated vasodilation. The goal of this study was to determine whether CRP also affects endothelial arachidonic acid (AA)-prostanoid pathways for vasomotor regulation. Porcine coronary arterioles were isolated and pressurized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The released superoxide, following ET-1 stimulation, can be converted to H 2 O 2 by superoxide dismutase or to peroxynitrite after reaction with NO. Since both H 2 O 2 and peroxynitrite have been shown to impair endothelium-dependent NO-mediated vasodilation in coronary arterioles [29, 51], the observed adverse effect of ET-1 in the present study might be the consequence of the formation of H 2 O 2 and/or peroxynitrite. However, administration of reported effective concentrations of scavengers for H 2 O 2 (i.e., catalase) [51] and peroxynitrite (i.e., urate) [29] did not protect the vessels from ET-1 insult (Fig.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The released superoxide, following ET-1 stimulation, can be converted to H 2 O 2 by superoxide dismutase or to peroxynitrite after reaction with NO. Since both H 2 O 2 and peroxynitrite have been shown to impair endothelium-dependent NO-mediated vasodilation in coronary arterioles [29, 51], the observed adverse effect of ET-1 in the present study might be the consequence of the formation of H 2 O 2 and/or peroxynitrite. However, administration of reported effective concentrations of scavengers for H 2 O 2 (i.e., catalase) [51] and peroxynitrite (i.e., urate) [29] did not protect the vessels from ET-1 insult (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…To examine whether the effect of ET-1 is affected by the inhibition of NO synthase (NOS), the vasodilations to serotonin and adenosine were examined in the presence of ET-1 and NOS inhibitor L-NAME (10 μmol/L) [24]. The involvements of superoxide, hydrogen peroxide (H 2 O 2 ) and peroxynitrite in the adverse effect of ET-1 were also examined by co-incubating the vessels with ET-1 plus superoxide scavengers Tempol (1 mmol/L) [28, 29] or MnTBAP (10 μmol/L) [30], H 2 O 2 scavenger catalase (1,000 units/mL) [31], and peroxynitrite scavenger urate (0.1 mmol/L) [29] for 60 minutes, respectively. To determine the contribution of superoxide generation enzyme NADPH oxidase (NOX) in mediating the ET-1 effect, vasodilations to serotonin and adenosine were studied in separate groups of vessels treated with ET-1 (0.1 nmol/L) in combination with NOX inhibitor apocynin (100 μmol/L) [28], VAS2870 (10 μmol/L) [32], NOX2-based assembly inhibitor gp91 ds-tat (10 μmol/L) [33] or Rac1/NOX2 inhibitor mycophenolic acid (10 μmol/L, Santa Cruz Biotechnology) [34].…”
Section: Methodsmentioning
confidence: 99%
“…Increased hs-CRP levels resulted in impaired endothelial function and lead to decrease in expression of endothelial-mediated NO and prostacyclin [24]. In addition, previous evidence suggests that NO has a positive modulation over both angiogenesis and arteriogenesis, which are the main contributors of coronary collateral circulation (CCC) development [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of this relation with long-term prognosis is unclear but endothelial dysfunction is the implied mechanism. Elevated hs-CRP levels lead to reduction of endothelial production of NO and prostacyclin, up-regulation of endothelial adhesion molecules, generation of superoxide in vascular cells, all of which elicit endothelial dysfunction (45). Previously, a study has demonstrated that high levels of hs-CRP are correlated with poor collateral circulation (46).…”
Section: Discussionmentioning
confidence: 99%